DISTRIBUSI PENDAPATAN DAN KEMISKINAN (BEBERAPA KAJIAN KEBIJAKAN) - Jacob Makapedua; Christien Karambut; Cysca Langi (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2023)
Abstract The purpose of this social economic study is to provide some understanding of the problems faced by the Indonesian nation in its efforts to achieve the goals of prosperity and welfare for all its people. There are several different views of economists and business practitioners in addressing the problems faced by the Indonesian people in achieving this lofty goal, such as poverty alleviation and unequal income distribution. Ideally, income distribution is a way in which national wealth/income is distributed among various factors of production that contribute to equal distribution of income for the people and can contribute to improving people's welfare. Income distribution is a very important issue for a country and should be the main focus of the government in ensuring the fulfillment of the needs of its people. Industrialization and increasing state investment are indeed important in economic development, but the way in which state income is distributed fairly is also important. Several policies deemed necessary to be followed up on problems of inequality in income distribution and poverty include the use of labor intensive rather than capital intensive production methods in several production sectors. Increasing state investment in the field of human resources to increase human resource competency capabilities which will later increase the nation's competitiveness, focus on development of the small and medium business sector which can drive the people's economy and implement progressive tax policies, especially for people with high incomes. Keywords: income distribution, poverty, economic development policies Abstrak Tujuan kajian ekonomi kemasyarakatan ini untuk memberikan beberapa pemahaman tentang permasalahan yang dihadapi bangsa Indonesia dalama upayanya mencapaian tujuan kemakmuran dan kesejahteraaan bagi seluruh rakyatnya. Terdapat beberapa perbedaan pandangan para ekonom dan praktisi bisnis dalam menyikapi permasalahan yang dihadapi bangsa Indonesia dalam mencapai tujuan luhur ini seeperti pengentasan kemiskinan dan distribusi pendapatan yang tidak merata. Idealnya distribusi pendapatan adalah suatu cara dimana kekayaan/pendapatan nasional didistribusikan keberbagai faktor produksi yang memberikan kontribusi terhadap pemeratan penddapatan bagi rakyatnya serta dapat berkontribusi pada peningkatan kesejahteraan rakyat. Distibusi pendapatan merupakan masalah yang sangat penting, bagi suatu negara dan seharusnya menjadi focus utama pemerintah dalam menjamin pemenuhan kebutuhan rakyatnya. Industrialisasi dan peningkatan investasi negara memang penting ddalam pembangunan ekonomi tetapi cara pendistribusian pendapatan negara secara adil juga adalah penting. Beberapa kebijakan yang dianggap perlu untuk ditindaklanjuti terhadap permasalahan ketimpangan distribusi pendapatan dan kemiskinan antara lain penggunaaan metode produksi yang berbasis pada labour intensive daripada capital intensive pada beberapa sektor produksi. Peningkatan investasi negara pada bidang human resources untuk meningkatakan kemapuan kompetensi sumberdaya manusia yang nantinya akan meningkat daya saing bangssa, focus pengembangan pada sektor usaha kecil dan menengah yang mdapat menggerak ekonomi rakyat serta menerapkan kebijakan pajak yang progresif terutama untuk masyarakat yang berpendapatan tingggi. Kata kunci: distribusi pendapatan, kemiskinan, kebijakan pembangunan ekonomi kemasyarakatan